IDEOLOGICAL IMMUNITY – A FACTOR IN PROTECTING YOUTH FROM IDEOLOGICAL ASSAULTS - Khujanova Tamara Juraevna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This article explores the concept of ideological immunity as a critical factor in shielding youth from various ideological assaults. It begins with a comprehensive definition of ideological immunity, emphasizing its role in fostering resilience against pervasive and potentially harmful ideologies. The paper discusses the mechanisms through which young individuals develop ideological resilience, including education, critical thinking skills, and exposure to diverse perspectives. Furthermore, it examines the influence of media, social networks, and peer interactions in shaping or challenging these ideological stances. The article highlights the importance of a multi-faceted approach that combines educational strategies, community involvement, and policy interventions to effectively enhance ideological immunity among youth, thereby safeguarding them from extremist and manipulative ideologies. The implications for policy makers, educators, and media practitioners are also discussed, providing a roadmap for cultivating a robust ideological defense in the younger generation.